Strengthening Legal Awareness Education on Environmental Permits Through Fiqh al-Bi’ah for Sustainable Fisheries Governance - Azka Nadhira; Aditya Prastian Supriyadi; Dwi Hidayatul Firdaus; Miftahul Huda (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Fishery enterprises in Jember Regency demonstrate low compliance with environmental permit regulations under Government Regulation No. 22/2021. This situation reflects the suboptimal performance of the Jember Regency Environment Agency in delivering legal the Jember Regency Environment Agency in delivering legal education. This condition is reflected in the ongoing operation of illegal shrimp farms, which have a negative impact on the environment and the surrounding residents. This research aims to analyze the urgency of legal awareness education regarding environmental permits, as conducted by the Jember Regency Environment Agency, in managing illegal and environmentally harmful fisheries, and to review it from the perspective of Fiqh al-Bi’ah. The study employs an empirical juridical method. Data collection techniques include interviews, observations, and documentation as primary sources, supported by literature and statutory materials as secondary sources. The findings reveal that legal education provided by the Environment Agency plays a crucial role in promoting compliance with environmental regulations among fishery business actors.. In the concept of Fiqh al-Bi’ah, education is a persuasive effort before the imposition of sanctions, aiming to cultivate awareness that protecting the environment is an act of worship and a moral responsibility of humans as caliphs on earth. This study contributes to enriching the understanding of legal awareness education by emphasizing ethical values within Fiqh al-Bi’ah as the basis for fostering compliance and promoting sustainable environmental and economic development.